Predictive Ability of Assertiveness and Emotional Intelligence on Marital Adjustment among Married Couples in Ibadan, Nigeria - Uye, Emmanuel; Okpara, Solomon C; Olapegba, Peter O (Indonesian Journal of Behavioral Studies, 2023)
Abstract This study examined assertiveness and emotional intelligence as predictors of marital adjustment among married couples in Greater Ibadan Municipality, Oyo State, Nigeria. The study adopted cross-sectional survey design and used purposive sampling technique to select five local government areas from the Greater Ibadan Municipality. Data were conveniently gathered from 395 participants using Assertiveness Scale, Emotional Intelligence Scale and Marital Adjustment Scale. Data collected were analysed using multiple regression and t-test of independent samples to test three hypotheses at a p < 0.05 level of significance. The result indicated that assertiveness and emotional intelligence jointly predicted marital adjustment among study participants (β = 0.27, F (2, 292) = 38. 52, p < 0.05). Also, assertiveness (β = 0.20, p < 0.05) and emotional intelligence (β = 0.29, p < 0.05) independently predicted marital adjustment among married couples in the study population. However, gender did not influence marital adjustment among study participants. The study concluded that couples’ assertiveness and emotional intelligence are strong predictors of marital adjustment. Therefore, the study recommended that marriage counsellors should assist both potential and old married couples in assertive and emotional training to be able to manage conflicts as it arises in their marriage. Keywords: Assertiveness; Emotional intelligence; Marital adjustment; Ibadan municipality; Nigeria.